Female labour supply and spousal education - Kerry L. Papps (Institute for the Study of Labor (IZA), 2010)
Three hypotheses are given to explain why a married woman's work hours might be related to her husband's education, even controlling for his wage rate. Data for a single cohort of women from the NLSY 1979 suggest that women's work hours are positively related to spousal education at the time of marriage but also fall more rapidly over time after marriage among those with the most educated husbands. Cross-sectional data from the CPS for 1980-2010 indicate that the latter effect appears to have increased since 2000. Both men's and women's preferences for a traditional division of labour within the household are found to be negatively related to the husband's education among newlyweds but to rise faster over the course of a marriage when the husband is highly educated. Overall, the results provide evidence consistent with both marital sorting on the basis of attitudes to female work and changes in tastes that are influenced by marital quality. Little support is found for the argument that spousal education measures non-market productivity.
Keywords: J16; J22; J24; 330; labour supply; households; education